Influence of the Digital Anatomist Foundational Model on traditional representations of anatomical concepts. - Agoncillo, A. V. (American Medical Informatics Association, 1999)
A principled and logical representation of the structure of the human body has led to conflicts with traditional representations of the same knowledge by anatomy textbooks. The examples which illustrate resolution of these conflicts suggest that stricter requirements must be met for semantic consistency, expressivity and specificity by knowledge sources intended to support inference than by textbooks and term lists. These next-generation resources should influence traditional concept representation, rather than be constrained by convention.